2016
DOI: 10.1093/cid/ciw650
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Adherence to Combination Antiretroviral Therapy Is Associated With Higher Levels of Inflammation Despite HIV Suppression

Abstract: Higher concentrations of inflammatory biomarkers were observed among HIV RNA-suppressed men who reported <100% cART adherence than among more adherent men. Residual HIV replication (ie, below the limit of detection), more likely among men with suboptimal adherence, is a plausible mechanism. Whether improving cART adherence could affect residual inflammation and associated morbidity and mortality rates should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 39 publications
5
75
0
3
Order By: Relevance
“…In fact, D‐dimer showed a trend towards lower plasma concentrations in children and young adults randomized to weekends off efavirenz‐based ART in one of these studies , which was unexpected, but similar to our findings of lower D‐dimer in sub optimally adherent participants in START. Among the possible explanations for these different findings is that the patients selected for inclusion in these studies constituted a population with long‐standing virologic suppression, which differs from the study populations evaluated in previous studies where adherence and inflammation were associated . Alternatively, the periods off ART (and their consequential decrease in drug exposure) that were instituted in these studies were predictable and cyclic, in comparison with the more erratic and irregular variations in ART adherence that are expected (and have been observed) in clinical and research cohorts.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, D‐dimer showed a trend towards lower plasma concentrations in children and young adults randomized to weekends off efavirenz‐based ART in one of these studies , which was unexpected, but similar to our findings of lower D‐dimer in sub optimally adherent participants in START. Among the possible explanations for these different findings is that the patients selected for inclusion in these studies constituted a population with long‐standing virologic suppression, which differs from the study populations evaluated in previous studies where adherence and inflammation were associated . Alternatively, the periods off ART (and their consequential decrease in drug exposure) that were instituted in these studies were predictable and cyclic, in comparison with the more erratic and irregular variations in ART adherence that are expected (and have been observed) in clinical and research cohorts.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, while recent research has suggested that improved ART regimens with higher genetic barrier may allow for lower levels of consistent adherence than those historically required (≥95%) to achieve viral suppression, the evidence for PWUD is scant and inconclusive [55, 56]. In addition, emerging studies also suggest that these sub-optimal levels of adherence may result in higher levels of immune activation and inflammation and increased non-AIDS related morbidity [57]. Our review also points to the lack of long-term benefits of any of the individual-level adherence interventions, and the absence of studies evaluating structural-level interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of adherence in the setting of virologic suppression: An emerging body of literature supports the concept that suboptimal adherence, in the context of virologic suppression, has significant clinical consequences as it relates to residual viral replication[118, 119] and higher levels of biomarkers of inflammation and coagulopathy[120–122]. Thus, an objective and reliable estimation of adherence in the virologically-suppressed population remains of critical importance.…”
Section: Potential Uses Of New Measures In Research and Clinical Scenmentioning
confidence: 99%